Protein structure principles - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Primary protein structure, X-ray diffraction and protein 3D structure, Interactions within proteins, Peptide bond constraints, Ramachandran maps
Reviewed at 2022/11/27